2015
DOI: 10.1002/phar.1586
|View full text |Cite
|
Sign up to set email alerts
|

A Descriptive and Historical Review of Bibliometrics with Applications to Medical Sciences

Abstract: The discipline of bibliometrics involves the application of mathematical and statistical methods to scholarly publications. The first attempts at systematic data collection were provided by Alfred Lotka and Samuel Bradford, who subsequently established the foundational laws of bibliometrics. Eugene Garfield ushered in the modern era of bibliometrics with the routine use of citation analysis and systematized processing. Key elements of bibliometric analysis include database coverage, consistency and accuracy of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
177
0
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 320 publications
(221 citation statements)
references
References 42 publications
1
177
0
11
Order By: Relevance
“…Bibliometric analysis is a tool used to assess the quantity and quality of research output on a certain topic (Thompson and Walker 2015). Bibliometric analysis on medicine-related poverty literature will give an idea on the volume of literature on this topic and content of articles that are being mostly cited in this field.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bibliometric analysis is a tool used to assess the quantity and quality of research output on a certain topic (Thompson and Walker 2015). Bibliometric analysis on medicine-related poverty literature will give an idea on the volume of literature on this topic and content of articles that are being mostly cited in this field.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, bibliometric analysis will shed light on network of authors and co-authorship that will help finding research partners across the globe for potential collaboration and joint grant seeking. Bibliometric analysis is also an important indicator of the impact of governmental and non-governmental initiatives on war against poverty and its consequences (Thompson and Walker 2015; Thompson and Clark 2015). Therefore, the objective of this study was to give a bibliometic overview on medicine-related literature on poverty using Scopus search engine.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that these metrics could be used by universities in promotion and tenure standards or by funding entities to measure research success. 19 Therefore, authors who wish to have their information most easily retrievable by MeSH terms might consider this delay when selecting a target journal and/or consider other platforms to highlight work.…”
Section: Discussionmentioning
confidence: 99%
“…The study also did not evaluate any differences between publication types. However, existing research in the pharmacy literature has suggested that time-toindexing did not vary between publication types 19 and authors anecdotally noted the majority of indexing occurred by journal issue.…”
Section: Study Limitationsmentioning
confidence: 98%
“…A bibliometric analysis is a statistical method to analyze literature to depict the development trends of knowledge and other information (such as citation information, authorship, and keyword co-occurrence). It is also useful to provide progress or indicators of developmental trends in the science publications [9]. …”
Section: Methodsmentioning
confidence: 99%